Best Answer

There are numerous solutions to the formula A + BA + C = A + BC, some of them are:

* (0,1,1) * (5,2,10) * (4,5,5) * (7,8,8) * (3,4,4) * (6,3,9)

User Avatar

Wiki User

14y ago
This answer is:
User Avatar
Study guides


20 cards

A polynomial of degree zero is a constant term

The grouping method of factoring can still be used when only some of the terms share a common factor A True B False

The sum or difference of p and q is the of the x-term in the trinomial

A number a power of a variable or a product of the two is a monomial while a polynomial is the of monomials

See all cards
3024 Reviews

Add your answer:

Earn +20 pts
Q: A plus BA plus C equals A plus BC?
Write your answer...
Still have questions?
magnify glass
Related questions

How is a plus b over a minus b equals c plus d over c minus d?

(a + b)/(a - b) = (c + d)/(c - d) cross multiply(a + b)(c - d) = (a - b)(c + d)ac - ad + bc - bd = ac + ad - bc - bd-ad + bc = -bc + ad-ad - ad = - bc - bc-2ad = -2bcad = bc that is the product of the means equals the product of the extremesa/b = b/c

5a plus d - bc equals a equals 5 b equals 7 c equals 2 d equals 4 what is the correct answer?


What is the simplified solution to BC plus 0 equals f?

f = B x C

If a plus b equals c and b plus c equals d and c plus d equals e and a equals 7 and e equals 5 what is a plus b plus c plus d plus e equal?

the answer is a

Rays BA and BC such that B is between A and C?

A Line Bisector

What happens when a nonmetal combines with another nonmetal?

A + bc - c + ba

Which if the following is a factor b squared plus bc munus 2c squared equals?

(b + 2c)(b - c)

If we know that AB plus BC equals AC then what would be a conclusion?

You could conclude that B lies between A and C.

A plus b plus c whole square?

(a+b+c) 2=a2+ab+ac+ba+b2+bc+ca+cb+c2a2+b2+c2+2ab+2bc+2ca [ ANSWER!]

1 plus x equals b c plus x equals d d plus x equals 89 b plus x equals c d equals?

1+x=dd+x so dd=1 so d=1 1+x=89b+x so 89b=1 so b=1/89 bc+x=1+x so bc=1 so c=1/(1/89) = 89 so cd=89 (and x=88)

If a plus b plus c not equal to 0 then a divided by b plus c equals b divided by c plus a equals c divided by a plus b prove that a equals b equals c?

Because there is no way to define the divisors, the equations cannot be evaluated.

If a plus a equals b and b plus c equals a and a-c equals b what is c?

a= (+a) or a= (-) b= 2a b= 2a c= (-a) c= (+a)